2015
DOI: 10.1186/s12960-015-0044-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring competing experiences and expectations of the revitalized community health worker programme in Mozambique: an equity analysis

Abstract: IntroductionMozambique launched its revitalized community health programme in 2010 in response to inequitable coverage and quality of health services. The programme is focused on health promotion and disease prevention, with 20 % of community health workers’ (known in Mozambique as Agentes Polivalentes Elementares (APEs)) time spent on curative services and 80 % on activities promoting health and preventing illness. We set out to conduct a health system and equity analysis, exploring experiences and expectatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Some CHWs have additional roles of providing treatment for basic clinical conditions and minor ailments such as malaria and diarrhoea [ 15 , 38 , 39 , 44 , 55 , 95 , 99 , 122 ]. Other CHWs provide basic obstetric case management but the CHWs providing this have completed post-secondary formal training in order to provide these services [ 28 , 30 , 32 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some CHWs have additional roles of providing treatment for basic clinical conditions and minor ailments such as malaria and diarrhoea [ 15 , 38 , 39 , 44 , 55 , 95 , 99 , 122 ]. Other CHWs provide basic obstetric case management but the CHWs providing this have completed post-secondary formal training in order to provide these services [ 28 , 30 , 32 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Kenya, the gender preferences seemed to be mixed. In Mozambique, unrealistic expectations from the community regarding curative tasks of APEs were more profound than in the other countries (Give et al, 2015). This could be a result of health facilities being less accessible: Mozambique has the largest catchment population per CHW, while the country has a challenging topography.…”
Section: Discussionmentioning
confidence: 99%
“…Elements of CHW programme design such as support, accountability and communication structures can influence relationships. When those structures do not function optimally, CHWs can face significant challenges in building trusting relationships with community members and actors in the health sector, leading to demotivation and tensions as a result of trying to accommodate conflicting interests and expectations (Give et al, 2015;Kok, Kea, et al, 2015;Maes & Kalofonos, 2013). Similarly, when contextual issues such as gender norms are ignored, relationships may be undermined as well (Viswanathan et al, 2012).…”
mentioning
confidence: 99%
“…Qualitative research in Mozambique by Give et al [ 2 ] also reveals how demand and supply factors interplay to shape the APE’s task prioritisation and hence impact on health equity. Give et al [ 2 ] argue that APEs found themselves caught between community demands for broader curative services while the official policy largely limits their focus. APEs showed agency in co-constructing a middle path acceptable to all.…”
Section: The Critical Role Of Programme Design Motivation and Incentmentioning
confidence: 99%
“…APEs showed agency in co-constructing a middle path acceptable to all. Saprii et al, Kok et al and Give et al [ 2 , 4 , 6 ] demonstrate the impact of weak health systems on CTC provider credibility and ability to fulfil their role. For example, in India, the health centres that ASHAs link to are ill-equipped and poorly functioning with negative consequences for the ASHA’s ability to inspire trust and credibility in the community [ 6 ].…”
Section: The Critical Role Of Programme Design Motivation and Incentmentioning
confidence: 99%